The influence of Bouba- and Kiki-like shape on perceived taste of chocolate pieces - Ogata, Kazuhiro; Gakumi, Reo; Hashimoto, Atsushi; Ushiku, Yoshitaka; Yoshida, Shigeo (Frontiers in Psychology, 2023)
In this paper, we present the findings of a study investigating the impact of shape on the taste perception of chocolate. Previous research has explored the influence of various sensory information on taste perception, but there has been little focus on the effect of food shape being eaten on taste perception. To explore this, we focused on the Bouba-Kiki effect, illustrating an interaction between shape and several modalities, and investigated the effect of Bouba- and Kiki-shaped (rounded and angular) foods eaten on taste perception. We utilized a 3D food printer to produce four different shapes of chocolate pieces based on the Bouba-Kiki. Participants tasted each piece and completed a chocolate flavor questionnaire. With Bayesian analysis, we determined that the Bouba-shaped chocolate pieces were perceived as sweeter than the Kiki-shaped ones, supporting earlier studies on crossmodal correspondences between shape and taste perception. However, there were no significant differences in ratings of other tastes, such as sourness and bitterness. Our research indicates that shape can affect taste perception during consumption and suggests that 3D food printers offer an opportunity to design specific shapes that influence taste experiences.